Analysis of pendulums coupled by torsional springs for energy harvesting - Michael Friswell (MATEC Web of Conferences, 2018)
Harvesting energy from ambient sources has been a recent topic of interest. A typical linear harvester is effective only near resonance, limiting its frequency bandwidth. In order to increase the efficiency and bandwidth of harvesters, various strategies have been proposed. Using multiple harvesters in a single device can harvest enough power over wider frequency band. In the present work, the effect of torsional coupling of the harvesters for low frequency vibration energy harvesting is investigated. Two pendulums with electromagnetic induction as the energy conversion mechanism is proposed. The performance of the device is studied theoretically and numerically. Cubic polynomials are used to model the pendulum nonlinearity. Fundamental harmonic oscillation are assumed to obtain the analytical solution. The effect of torsional coupling and pendulum length on the power harvested are reported.